2002
DOI: 10.1258/0022215021910519
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and ultrasonographic evaluation of metastatic cervical lymph nodes with surgicoclinicopathologic correlation

Abstract: The detection of cervical lymph nodal metastasis and carotid artery invasion by metastatic lymph nodes is an important issue in the management of head and neck malignancies. This study compared the evaluation of metastasis by palpation, ultrasonography (USG) and computed tomography (CT) in patients with known head and neck malignancies. Twenty-five consecutive patients with head and neck malignancy were prospectively evaluated for the presence of cervical lymphadenopathy and carotid artery invasion. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 16 publications
(30 reference statements)
6
45
0
1
Order By: Relevance
“…These results go in accordance with the observations made by Van den Brekel [23] and Sarvanan et al [17]. Sarvanan et al [17] suggested that the presence of central necrosis was the most specific sign of metastatic lymphadenopathy. They reported 100% sensitivity and specificity for central nodal necrosis criteria.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results go in accordance with the observations made by Van den Brekel [23] and Sarvanan et al [17]. Sarvanan et al [17] suggested that the presence of central necrosis was the most specific sign of metastatic lymphadenopathy. They reported 100% sensitivity and specificity for central nodal necrosis criteria.…”
Section: Discussionsupporting
confidence: 92%
“…They noted the decrease of false positive results from 63% to 5% using the L/S ratio. Sarvanan et al [17] have showed similar sensitivity (94.44%) and higher specificity (100%) than that reported by Steinkamp et al [18].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Many papers [4][5][6]12,[16][17][18] have described CT as the best method for image-based staging of cervical lymph nodes. These studies compared image findings with pathology lab findings, obtaining good sensitivity and specificity values in staging cervical lymph nodes, and consequently, their relation with the carotid artery.…”
Section: Discussionmentioning
confidence: 99%